1975
DOI: 10.1056/nejm197505292922204
|View full text |Cite
|
Sign up to set email alerts
|

Total Eosinophil Counts in the Management of Bronchial Asthma

Abstract: Total eosinophil counts were investigated in asthmatic patients to determine their usefulness in the diagnosis and management of steroid-dependent asthma. Counts averaged 122 plus or minus 74 (S.D.) per mm-3 (65 untreated normal subjects) and 43 plus or minus 22 per mm-3 (six prednisone-treated normal subjects). Fifty-two patients with active bronchial asthma showed significant eosinophilia (greater than 350/mm-3 off and greater than 85/mm-3 on steroids), suggesting that eosinophilia is an important diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
136
1
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(150 citation statements)
references
References 12 publications
9
136
1
1
Order By: Relevance
“…Whether these differences represent different dose effects, differences in duration of action or other actions of the drugs is not clear at present. Our observations are consistent with the available clinical observations that a reduction of eosinophils in blood, sputum or lungs occurs in atopic asthmatic patients following treatment with cromoglycate (Diaz et al, 1984) or ketotifen (Gobel, 1978) and in patients with intrinsic bronchial asthma when treated with glucocorticosteroids (Horn et al, 1975). Furthermore, theophylline and glucocorticosteroids, but not cromoglycate or salbutamol, inhibit the production of an eosinophil-activating factor by peripheral blood monocytes obtained from individuals with moderate eosinophilia (Thorne et al, 1988).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Whether these differences represent different dose effects, differences in duration of action or other actions of the drugs is not clear at present. Our observations are consistent with the available clinical observations that a reduction of eosinophils in blood, sputum or lungs occurs in atopic asthmatic patients following treatment with cromoglycate (Diaz et al, 1984) or ketotifen (Gobel, 1978) and in patients with intrinsic bronchial asthma when treated with glucocorticosteroids (Horn et al, 1975). Furthermore, theophylline and glucocorticosteroids, but not cromoglycate or salbutamol, inhibit the production of an eosinophil-activating factor by peripheral blood monocytes obtained from individuals with moderate eosinophilia (Thorne et al, 1988).…”
Section: Discussionsupporting
confidence: 91%
“…Eosinophil numbers in peripheral blood can be used as an index of disease severity in bronchial asthma (Horn et al, 1975;Brown et al, 1977) and the occurrence of eosinophils in bronchoalveolar lavage (BAL) fluid has been reported to precede late-onset responses to allergen in asthma patients (De Monchy et al, 1985). However, only recently has the contribution of the eosinophil to the pathology of asthma been emphasised (Dahl & Venge, 1982;Frigas & Gleich, 1986).…”
Section: Introduction Antiseramentioning
confidence: 99%
“…Elevated eosinophil counts in blood and sputum is associated with disease severity [13,14]. As early as 1975, Horn et al [15] observed that increased blood eosinophil counts correlate with increasing airway obstruction in patients undergoing a pulmonary function test. Since then, several observational studies have also revealed that increased blood eosinophils are associated with more severe airflow obstruction [16], more severe exacerbations [1720], lower odds of achieving asthma control [1719,21], and increased hospital costs [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Increased eosinophil numbers in peripheral blood, sputum or lung tissue are now widely acknowledged to be characteristic of asthma (Dunnill, 1960;Epstein, 1972;Horn et al, 1975;Frigas & Gleich, 1986). In addition, toxic eosinophil products, such as major basic protein (MBP) (Frigas et al, 1981) and eosinophil cationic protein (ECP) (Dahl et al, 1978) have been demonstrated in the sputum and blood of asthma patients.…”
Section: Introductionmentioning
confidence: 99%